The Challenge of Superhydrophobicity: Environmentally Facilitated Cassie–Wenzel Transitions and Structural Design - Xin Zhong; Shangzhen Xie; Zhiguang Guo (Advanced Science, 2024)
Abstract Superhydrophobic materials can be used in various fields to optimize production and life due to their unique surface wetting properties. However, under certain pressure and perturbation conditions, the droplets deposited on superhydrophobic materials are prone to change from Cassie state to Wenzel state, which limits the practical applications of the materials. In recent years, a large number of works have investigated the transition behavior, transition mechanism, and influencing factors of the wetting transition that occurs when a superhydrophobic surface is under a series of external environments. Based on these works, in this paper, the phenomenon and kinetic behavior of the destruction of the Cassie state and the mechanism of the wetting transition are systematically summarized under external conditions that promote the wetting transition on the material surface, including pressure, impact, evaporation, vibration, and electric wetting. In addition, superhydrophobic surface morphology has been shown to directly affect the duration of the Cassie state. Based on the published work the effects of specific morphology on the Cassie state, including structural size, structural shape, and structural level, are summarized in this paper from theoretical analyses and experimental data.